PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF DAN KOMPETITIF DALAM MENGEMBANGKAN KREATIVITAS SISWA - Aziz, Rahmat (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2008)
Both cooperative and competitive methods are influence the student creativity. However, base on the research study the cooperative method understood is more effective than competitive method in developing student creativity. Therefore, using both methods (cooperative and competitive) should be tried in learning process in classes. Keyword: Learning, Cooperative, Competitive, Creativity